A place in the sun : Marxism and Fascism in China's long revolution - Gregor, A. James (Anthony James), 1929- (Westview Press, 2000)
"In A Place in the Sun, A. James Gregor offers an interpretation of the role of European marxist and fascist ideas on China's revolutionaries that is both original and based on a lifetime of scholarship devoted to revolutionary ideologies. Gregor renders a detailed analysis of their respective influence on major protagonists. In the exposition, Gregor reveals an unsuspected and complex set of relationships between the Chinese revolution and essentially European ideologies. His discussion concludes with a number of estimations that suggest implications for the future of modern China and its relationship with the advanced industrial democracies.